Effects of exogenous gibberellic acid on reproductive organ development in maize inbred lines with differences in light sensitivity under weak light conditions - Zhixian Zhong; Jianjun Fu; Jisen Li; Wanli Du; Min Zhu; Wei Xue; Xuemei Zhong; Jianzhou Qu (Plant Stress)
In order to clarify the regulatory effects of externally applying gibberellic acid (GA3) on different light-sensitive inbred maize lines under weak light conditions, we used two light-sensitive maize inbred lines as experimental materials, SN98A (light-sensitive inbred line) and SN98B (light-insensitive inbred line), and compared the reproductive organ development process after treatment with different concentrations of GA3 (20, 40, and 60 mg L–1) under 38 % shading conditions. We analyzed the regulatory mechanisms associated with the effects of exogenous GA3 on maize ear development under weak light. The results showed that under weak light, the light-tolerant SN98B maintained complete reproductive success (barren stalk rates < 10 %) in both control and GA3-treated groups, demonstrating inherent stress tolerance. For the light-sensitive inbred line SN98A, the external application of GA3 significantly increased the endogenous GA3 content in SN98A. In addition, applying GA3 improved the stem segment vascular bundle and garland structure in SN98A under weak light, as well as promoting the development of male and female panicles, and increasing the length of the main panicle, number of branches, number of florets, amount of pollen, and the number of filaments in the female panicle, and enhancing the pollen and filament vitality. Applying GA3 improved the pollination efficiency and reduced the barren rate in SN98A, where 60 mg L–1 GA3 had the greatest effect.